Типифікація таксонів родини Asteraceae флори України; роди Jurinea Cass., Lagoseris M. Bieb., Lamyra (Cass.) Cass., Lapsana L., Leontodon L., Leucanthemum Mill., Ligularia Cass., Matricaria L., Onopordum L., Picris L., Ptarmica Neck., Pulicaria Gaertn., Pyrethrum Zinn - Шиян, Н.М.; Мосякін, С.Л.; Федорончук, М.М. (Український ботанічний журнал, 2012)
В статье изложены результаты типификации видов семейства Asteraceae из родов Jurinea,
Lagoseris, Lamyra, Lapsana, Leontodon, Leucanthemum, Ligularia, Matricaria, Onopordum, Picris,
Ptar mica, Pulicaria, Pyrethrum, описанных с территории Украины. Для каждого вида указаны
базионим, синонимика, протолог, номенклатурный тип и место его хранения. In the article results of typification of the Asteraceae species (from genera Jurinea, Lagoseris, Lamyra,
Lapsana, Leontodon, Leucanthemum, Ligularia, Matricaria, Onopordum, Picris, Ptarmica, Pulicaria,
Pyrethrum) described from Ukraine are given. For each species, the following data are provided: basionym; synonym, type according to the protologue, nomenclatural type and its location (herbarium).